Obtaining informed consent for genomics research in Africa: analysis of H3Africa consent documents. Issue 2 (7th December 2015) - Munung, Nchangwi Syntia; Marshall, Patricia; Campbell, Megan; Littler, Katherine; Masiye, Francis; Ouwe-Missi-Oukem-Boyer, Odile; Seeley, Janet; Stein, D J; Tindana, Paulina; de Vries, Jantina
Abstract : Background: The rise in genomic and biobanking research worldwide has led to the development of different informed consent models for use in such research. This study analyses consent documents used by investigators in the H3Africa (Human Heredity and Health in Africa) Consortium. Methods: A qualitative method for text analysis was used to analyse consent documents used in the collection of samples and data in H3Africa projects. Thematic domains included type of consent model, explanations of genetics/genomics, data sharing and feedback of test results. Results: Informed consent documents for 13 of the 19 H3Africa projects were analysed. Seven projects used broad consent, five projects used tiered consent and one used specific consent. Genetics was mostly explained in terms of inherited characteristics, heredity and health, genes and disease causation, or disease susceptibility. Only one project made provisions for the feedback of individual genetic results. Conclusion: H3Africa research makes use of three consent models—specific, tiered and broad consent. We outlined different strategies used by H3Africa investigators to explain concepts in genomics to potential research participants. To further ensure that the decision to participate in genomic research is informed and meaningful, we recommend that innovative approaches to the informed consent process be developed, preferably in consultation with research participants, research ethics committees and researchers in Africa.